2018
DOI: 10.1126/sciadv.aaq1360
|View full text |Cite
|
Sign up to set email alerts
|

A network approach to topic models

Abstract: A new approach to topic models finds topics through community detection in word-document networks.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
169
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(191 citation statements)
references
References 57 publications
2
169
0
1
Order By: Relevance
“…We used the Force Atlas 2 algorithm to structure the semantic network (Jacomy, Venturini, Heymann, & Bastian, ). To detect topics, we employed the Louvian method for community detection (Blondel, Guillaume, Lambiotte, & Lefebvre, ; Gerlach, Peixoto, & Altmann, ). We found that this approach detected topics better than the more common Latent Dirichlet Allocation topic modeling approaches (Hong & Davison, ) or the structural topic modeling approach (Roberts, Stewart, Tingley, & Airoldi, ; see Supplementary Information S1.3).…”
Section: Methodsmentioning
confidence: 99%
“…We used the Force Atlas 2 algorithm to structure the semantic network (Jacomy, Venturini, Heymann, & Bastian, ). To detect topics, we employed the Louvian method for community detection (Blondel, Guillaume, Lambiotte, & Lefebvre, ; Gerlach, Peixoto, & Altmann, ). We found that this approach detected topics better than the more common Latent Dirichlet Allocation topic modeling approaches (Hong & Davison, ) or the structural topic modeling approach (Roberts, Stewart, Tingley, & Airoldi, ; see Supplementary Information S1.3).…”
Section: Methodsmentioning
confidence: 99%
“…A pictorial representation of the activity of the user and the relationship between posts, pages and topics in reported in Figure 1. [22] . Single icons created using the free gallery of OpenOffice.…”
Section: A Users' News Consumptionmentioning
confidence: 99%
“…By representing the relationship between words and documents (posts in our case) as a bipartite network, the algorithm proposed by [22] detects communities (i.e. cluster of densely interconnected nodes) using a hierarchical Stochastic Block Modeling (hSBM) algorithm [33][34][35].…”
Section: A Topic Modeling Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…in Section 1.Before looking at SBMs with topic modelling for graph and textual data, it is useful to look at a recently proposed SBM for textual data byGerlach et al (2018). Instead of probabilitistically factorising the document-word frequency matrix M (Section 10), they treated the relations between the words and the documents as a bipartite graph, in which both the words and the documents are the nodes.…”
mentioning
confidence: 99%